Tungsten copper ultrathin sheet and preparation and application thereof

By using metal paste containing tungsten and simplifying the process flow, the problems of complexity and high energy consumption of existing tungsten copper alloy ultra-thin sheets are solved, and the tungsten copper ultra-thin sheet with high density and thermal conductivity are achieved, satisfying the Demand in the field of microelectronic packaging.

CN119274840APending Publication Date: 2025-01-07SHANGHAI LEADING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411415326.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing production methods of tungsten copper alloy ultra-thin sheets are complex, have high energy consumption, high cost and are difficult to meet the needs of high-end microelectronic packaging, especially in terms of W90Cu10 sheets with a thickness of 0.1mm.

Method used

Using tungsten-containing metal paste, including tungsten powder, aqueous polyurethane composition and thickener, through coating film formation, copper coating, degreasing sintering and cooling, tungsten copper ultra-thin sheets are obtained, simplifying the process flow, improving density and Thermal conductivity.

Benefits of technology

The high density (≥98.8wt.%) and excellent thermal conductivity (140-350W/m·K) of tungsten copper ultra-thin sheet are achieved, which reduces process complexity and energy consumption and meets the needs of the microelectronic packaging field. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119274840A_ABST
    Figure CN119274840A_ABST
Patent Text Reader

Abstract

The invention discloses a tungsten copper ultrathin sheet and preparation and application thereof, a tungsten film prepared from provided tungsten-containing metal slurry is high in solid content, the mass fraction of tungsten reaches up to 95 wt.%, the thickness size is as low as 0.1 mm, the width can be freely converted within 10-500 mm, and the technological requirements of die cutting, patterning, laminated pressing and the like can be met; the hardness is lower than 30 HA, the tensile yield strength is as high as 20 MPa, the elongation at break is as high as 350%, and excellent flexibility and mechanical properties are achieved. According to a tungsten copper sheet material product obtained through tungsten film copper coating, preparation of a tungsten copper sheet with the thickness of 0.1-1 mm, high density, high heat conduction and low expansion can be achieved without tedious deformation machining and large deformation, the density of the prepared tungsten copper sheet reaches up to 98.8 wt.% or above, the heat conduction coefficient of the tungsten copper sheet can reach 140-350 W / m.K, and the tungsten copper sheet can be used for manufacturing the tungsten copper sheet. The thermal expansion coefficient is lower, and the thermal expansion coefficient is 5.9-8.5 * 10 <-6 > / K. In addition, an independent degreasing process is not needed, the process is short, energy is saved, the environment is protected, and the sintering carbon content is lower than 0.008 wt.%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of manufacturing metal sheets, and in particular to the field of manufacturing an ultra-thin sheet of tungsten alloy. Background Art

[0002] With the rapid development of communication technology and integrated circuits, the types and number of electronic devices have increased dramatically, especially high-power devices, whose internal components are compact and have high heat flux density. These devices will generate a lot of heat energy during long-term operation. If the heat cannot be effectively dissipated, the performance of the electronic chip will be reduced, and may even cause serious problems such as thermal failure, short circuit or even fire. Therefore, high-performance heat dissipation materials are increasingly used in electronic devices, and the requirements for material thickness, density, air tightness, thermal conductivity and other performance are becoming increasingly stringent.

[0003] Tungsten copper (WCu) composite material has become a leader in heat dissipation materials due to its excellent thermal and electrical conductivity. It is composed of a tungsten component with a high melting point, high hardness, and low expansion and a copper component with high electrical conductivity and high thermal conductivity. By adjusting the ratio of tungsten and copper, its thermal conductivity and thermal expansion coefficient can be precisely controlled. This material is widely used in the field of heat dissipation because of its thermal expansion coefficient that matches that of substrates such as silicon, gallium arsenide and ceramics. However, the development of high-performance WCu materials still faces challenges, and the optimization of different components, thickness and density is crucial.

[0004] Since the melting points of tungsten and copper are very different, 3450℃ and 1083℃ respectively, traditional smelting methods are not applicable and can only rely on powder metallurgy technology for production. At present, the production methods of tungsten-copper alloy are mainly divided into two categories: one is tungsten powder compaction followed by copper infiltration, and the other is tungsten-copper mixed powder sintering followed by rolling. The former has difficulties in pressing tungsten films and sheets, and the molten-infiltrated state of tungsten-copper alloy is difficult to roll; the latter is prone to tungsten and copper enriched areas because the uniformity of powder mixing is difficult to ensure.

[0005] Patent CN104209532 uses a mixture of tungsten and copper powders and steel molded blanks with a thickness of 2-20 mm. The blanks are then subjected to multiple passes of hot rolling, warm rolling, cold rolling, and large deformation compression molding to ultimately obtain 0.1 mm thin sheets. The above process routes are complex, energy consuming, and have low yields. The molding process cannot be continuous, and the cost is high. Furthermore, after multiple hot rolling, warm rolling, and cold rolling, the grain size of the tungsten-copper thin sheet is large and anisotropic.

[0006] Therefore, the current market demand for high-end tungsten copper microelectronic packaging sheets is difficult to be effectively met. The existing preparation method mainly relies on grinding from thicker tungsten copper sheets, which is not only inefficient and costly, but also difficult to prepare ultra-thin sheets such as 6-inch and 8-inch sheets, especially W90Cu10 sheets with a thickness of only 0.1mm (for LEDs). Therefore, the development of large-size, high-thermal-conductivity, low-expansion tungsten copper alloy ultra-thin sheets suitable for the field of microelectronic packaging has become an urgent problem to be solved. Summary of the invention

[0007] A first aspect of the present invention provides a tungsten-containing metal slurry, comprising:

[0008] Tungsten powder, organic film former and thickener;

[0009] The organic film-forming agent includes an aqueous polyurethane composition;

[0010] The mass ratio of tungsten powder, organic film-forming agent and thickener is (80-95):(5-20):(2-5).

[0011] In a preferred embodiment, the aqueous polyurethane composition includes one or a combination of aqueous polyurethane emulsion (such as UW-1527DF, UW-1614AF), polyethylene glycol (such as PEG400).

[0012] Preferably, the aqueous polyurethane composition comprises UW-1527DF, UW-1614AF, and PEG400.

[0013] More preferably, the mass ratio of UW-1527DF, UW-1614AF and PEG400 is (40-80):(10-40):(2-15), preferably (50-75):(15-35):(3-12), and more preferably (60-70):(20-30):(5-10).

[0014] In a preferred embodiment, the particle D50 size (radius) of the tungsten powder is 0.5-6 μm, preferably 0.8-5 μm, and more preferably 1-3 μm.

[0015] In a preferred embodiment, the mass purity of the tungsten powder is ≧99.50wt.%, preferably ≧99.90wt.%, and more preferably ≧99.95wt.%.

[0016] In a preferred embodiment, the organic film-forming agent may further include one or more of a surfactant, a dispersant, a wetting agent, a leveling agent, and a defoaming agent.

[0017] Preferably, the mass ratio of the aqueous polyurethane composition to the surfactant in the organic film-forming agent is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), and more preferably (100-105):(0.5-1).

[0018] In a preferred embodiment, the surfactant in the organic film-forming agent includes one or more of anionic surfactants, cationic surfactants, and nonionic surfactants.

[0019] Preferably, the anionic surfactant includes one or more of sodium dodecyl sulfate, sodium alkylbenzene sulfonate, sodium tripolyphosphate, and sodium hexametaphosphate.

[0020] Preferably, the cationic surfactant includes one or more of dodecyldimethylbenzyl ammonium chloride, benzalkonium chloride, and dioctadecyldimethylammonium chloride.

[0021] Preferably, the nonionic surfactant includes one or more of fatty alcohol polyoxyethylene ether, ethylene glycol stearate, dodecyl alcohol, alkylphenol polyoxyethylene ether, and nonylphenol polyoxyethylene ether.

[0022] In a preferred embodiment, the mass ratio of the aqueous polyurethane composition to the dispersant in the organic film-forming agent is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), and more preferably (100-105):(0.5-1).

[0023] In a preferred embodiment, the dispersant in the film-forming agent includes one or more of sodium polyacrylate, polyvinyl pyrrolidone, tributyl phosphate, alkyl phosphate, aryl phosphate, monoethanolamine, diethanolamine, sodium silicate, and trisodium phosphate.

[0024] In a preferred embodiment, the mass ratio of the aqueous polyurethane composition to the wetting agent in the organic film-forming agent is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), and more preferably (100-105):(0.5-1).

[0025] In a preferred embodiment, the wetting agent in the organic film-forming agent includes one or more of alkyl sulfates, sulfonates, fatty acids or fatty acid ester sulfates, carboxylic acid soaps, phosphates, silicone oil-type wetting agents, aqueous wetting agents, and organic solvent wetting agents.

[0026] In a preferred embodiment, the mass ratio of the aqueous polyurethane composition to the leveling agent in the organic film-forming agent is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), and more preferably (100-105):(0.5-1).

[0027] In a preferred embodiment, the leveling agent in the organic film-forming agent includes one or more of silicone, polyacrylate, fluorine-containing polymer, and modified acrylate.

[0028] In a preferred embodiment, the mass ratio of the aqueous polyurethane composition to the defoaming agent in the organic film-forming agent is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), and more preferably (100-105):(0.5-1).

[0029] In a preferred embodiment, the defoaming agent in the organic film-forming agent includes one or more of silicone defoaming agents (such as TEGOFoamex 810, BYK-051), polyether defoaming agents (such as DC 2000, DF-1030), fatty acid and its derivatives defoaming agents (such as Span 80), polyacrylate defoaming agents, and mineral oil defoaming agents.

[0030] In a preferred embodiment, the mass ratio of the aqueous polyurethane composition to deionized water in the organic film-forming agent is (80-120):(1-40), preferably (85-110):(2-35), and more preferably (100-105):(3-30).

[0031] In a preferred embodiment, the thickener includes one or more of polyvinyl alcohol, polyacrylic acid, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, aluminum silicate, sodium silicate, bentonite, and associative waterborne polyurethane.

[0032] The second aspect of the present invention provides a method for preparing a tungsten-copper ultra-thin sheet, the steps comprising: coating the tungsten-containing metal slurry described in the first aspect of the present application to form a film, drying to obtain a tungsten film blank; copper coating the tungsten film blank, then degreasing, sintering, and cooling to obtain a tungsten-copper alloy;

[0033] The tungsten-copper alloy is rolled to obtain the tungsten-copper ultra-thin sheet.

[0034] In a preferred embodiment, in the preparation method, the process of making the tungsten film blank further includes: after the drying, a tungsten film coil is obtained, and the tungsten film coil is used to prepare a tungsten film blank having a preset shape.

[0035] Preferably, the tungsten film coil is processed by one or more of the methods such as die cutting, patterning, lamination pressing, etc. to obtain the tungsten film blank with the preset shape.

[0036] In a preferred embodiment, the die-cutting processing method is any one of laser cutting and die-cutting machine cutting. Preferably, the size of the die-cutting is any size.

[0037] In a preferred embodiment, the patterning process of the tungsten film coil is laser cutting.

[0038] Preferably, the structure of the pattern is any one or two of a circle, a hexagon, a triangle, a quadrilateral, an ellipse, a heart shape, etc.

[0039] Preferably, the diameter or side size of the pattern is 0.1-5 mm, preferably 0.1-3 mm, more preferably 0.1-2 mm.

[0040] Preferably, the interval size of the pattern is 0.1-5 mm, preferably 0.1-3 mm, more preferably 0.1-2 mm.

[0041] In a preferred embodiment, the thickness of the tungsten film coil is 0.01-1 mm, preferably 0.01-0.8 mm, and more preferably 0.01-0.5 mm.

[0042] In a preferred embodiment, the width of the tungsten film coil is 50-800 mm, preferably 100-600 mm, and more preferably 200-500 mm.

[0043] In a preferred embodiment, the coating process includes any one of a casting process and a slit coating process.

[0044] In a preferred embodiment, the drying temperature is 40-120°C, preferably 45-100°C, more preferably 50-90°C.

[0045] In a preferred embodiment, the tungsten content in the tungsten film blank is ≧90wt.%, preferably ≧92wt.%, and more preferably ≧95wt.%.

[0046] In a preferred embodiment, the tensile strength of the tungsten film blank is 15-35 MPa, preferably 18-30 MPa, and more preferably 20-25 MPa.

[0047] In a preferred embodiment, the elongation at break of the tungsten film blank is 200-450%, preferably 250-400%, and more preferably 350-380%.

[0048] In a preferred embodiment, the hardness of the tungsten film blank is 20-40HA, preferably 25-38HA, and more preferably 30-35HA.

[0049] In a preferred embodiment, the mass ratio of tungsten to copper in the tungsten-copper alloy is (20-98):(2-80), preferably (25-96):(4-75), and more preferably (30-95):(5-70).

[0050] In a preferred embodiment, the copper coating method is to lay copper foil flat on the upper surface of the tungsten film blank, wherein the size of the copper foil is consistent with the size of the tungsten film blank.

[0051] In a preferred embodiment, an inert gas or a reducing gas is used as a protective gas during the sintering process, for example, Ar, He, N2, H2 or any mixed gas thereof, for example, a mixed gas of N2 and H2 is used as a protective gas.

[0052] In a preferred embodiment, the sintering temperature is 800-1800°C, preferably 1000-1600°C, and more preferably 1200-1500°C.

[0053] In a preferred embodiment, the sintering is one or more of microwave sintering, push boat sintering, electric spark sintering, reaction sintering, hot pressing sintering, and isostatic pressing sintering.

[0054] Preferably, the pushing boat speed of the push boat sintering is 1-10 mm / min, preferably 1.5-8 mm / min, more preferably 2-5 mm / min.

[0055] In a preferred embodiment, the cooling temperature is 5-60°C, preferably 10-50°C, more preferably 20-40°C.

[0056] In a preferred embodiment, the total deformation amount of the rolling is 1-40%, preferably 3-30%, and more preferably 5-25%.

[0057] In a preferred embodiment, the deformation amount of each rolling pass is 0.2-8%, preferably 0.5-6%, and more preferably 1-5%.

[0058] In a preferred embodiment, the number of rolling passes is 1-40 times, preferably 1-30 times, and more preferably 1-20 times.

[0059] In a preferred embodiment, the thickness of the tungsten copper ultra-thin sheet is 0.02-2 mm, preferably 0.05-1.5 mm, and more preferably 0.1-1 mm.

[0060] In a preferred embodiment, the density of the tungsten-copper ultra-thin sheet is ≧95.5wt.%, preferably ≧97.5wt.%, and more preferably ≧98.8wt.%.

[0061] In a preferred embodiment, the thermal conductivity of the tungsten copper ultra-thin sheet is 100-400 W / m·K, preferably 120-380 W / m·K, and more preferably 140-350 W / m·K.

[0062] In a preferred embodiment, the thermal expansion coefficient of the tungsten copper ultra-thin sheet is 5-10*10 -6 / K, preferably 5.5-8.8*10 -6 / K, more preferably 5.9-8.5*10 -6 / K.

[0063] The third aspect of the present invention is to provide a use of a tungsten-copper ultra-thin sheet, which can be applied to the fields of heat sink materials and electronic packaging materials, especially to 4-12 inch microelectronic packaging.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] The present invention provides a tungsten-copper ultra-thin sheet, preparation and application thereof. The tungsten film prepared by the tungsten-containing metal slurry provided by the present invention has a high solid content, a tungsten mass fraction of up to 95wt.%, a thickness as low as 0.1mm, and a width that can be arbitrarily converted within 10-500mm, which can meet the process requirements of die cutting, patterning and lamination pressing; its hardness is lower than 30HA, the tensile yield strength is as high as 20MPa, and the elongation at break is as high as 350%, and it has excellent flexibility and mechanical properties. The tungsten-copper thin sheet material product obtained by copper coating the tungsten film can achieve a density of more than 98.8wt.% without rolling a large deformation, and its thermal conductivity can reach 140-350W / m·K, and the thermal expansion coefficient is 5.9-8.5*10 -6 / K. The present invention does not require a separate degreasing process, has a short process, is energy-saving and environmentally friendly, and has a sintered carbon content lower than 0.008wt.%. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 Schematic diagram of the tungsten film coil of the present invention.

[0067] Figure 2 Schematic diagram of tungsten film patterning according to the present invention.

[0068] Figure 3 Schematic diagram of scanning electron microscope of the tungsten copper ultra-thin sheet sample of the present invention. DETAILED DESCRIPTION

[0069] The present invention provides a tungsten copper ultra-thin sheet, preparation and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0070] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged under appropriate circumstances. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0071] The following examples are not intended to limit the present invention in any way.

[0072] Thermal diffusivity: Passed the ASTM E 1461-13 test.

[0073] Thermal Expansion Coefficient: Passed ASTM E831-19 test.

[0074] Hardness: Passed GB / T6739-1996 test.

[0075] Tensile properties (including tensile strength and elongation at break): passed the GB / T 19250-2013 test.

[0076] Embodiment 1:

[0077] In this embodiment, a W90Cu10 thin sheet is provided, and its preparation method comprises the following steps:

[0078] S1. Select tungsten powder: the tungsten powder is ordinary tungsten powder with a particle size D50 of 1-3μm, and it is ready for use;

[0079] S2, film-forming agent configuration: select 100 parts of waterborne polyurethane composition (including UW-1527DF, UW-1614AF, PEG400, wherein the mass ratio of UW-1527DF, UW-1614AF, PEG400 is 60:20:5), 1.0 part of surfactant dodecyl dimethyl benzyl ammonium chloride, and dispersant Solsperse TM W750.5 parts, wetting agent KMT-55140.5 parts, leveling agent KMT-55100.5 parts, defoaming agent DOWSIL85900.8 parts, deionized water 25 parts;

[0080] S3, metal slurry preparation: stir and disperse the materials of S1 and S2,

[0081] Among them, the material of S1 is 90 parts, the material of S2 is 8 parts, and the thickener Thadd108F is 2 parts;

[0082] S4, preparation of tungsten film: the material obtained in step S3 is coated by tape casting process to form a film, the wet film thickness is 0.5mm, the coating width is 350mm, and it is dried at 65°C to obtain a tungsten film coil with a thickness of 0.35mm; the performance of the tungsten film obtained in this embodiment is characterized, and it is found that it has a high solid content, the mass fraction of tungsten is as high as 95wt.%, the thickness is 0.35mm, and the width can be arbitrarily changed within 10-500mm; its hardness is less than 30HA, the tensile yield strength is as high as 20MPa, and the elongation at break is as high as 350%;

[0083] S5, tungsten film processing: the tungsten film coil obtained in step S4 is die-cut to obtain a tungsten film blank with a size of 350*150 mm;

[0084] S6, sintering treatment: the tungsten film blank obtained in step S5 is placed on an alumina ceramic plate, and the Cu foil is cut into the plane size described in S5 according to the mass ratio of tungsten to copper (W:Cu=90:10) and fixed on the tungsten film blank for push boat sintering. The sintering atmosphere is hydrogen obtained by decomposing ammonia, the sintering temperature is 1480°C, the push boat speed is 2.0mm / min, and then cooled to obtain a 90 tungsten copper sintered blank with a thickness of 0.32mm;

[0085] S7, rolling treatment: rolling the material obtained in step S6, with a total rolling deformation of 25%, a deformation of 1-3% per pass, and 10 rolling passes, to obtain W90Cu10 tungsten copper ultra-thin sheets with a thickness of 0.2 mm and a density of 98.8 wt.%.

[0086] The tungsten copper ultra-thin sheet obtained in this embodiment was characterized by SEM, and the test results are as follows: Figure 3 As shown, it can be seen that the tungsten grains in the tungsten-copper ultra-thin sheet obtained in this embodiment are small in size, evenly dispersed, and highly isotropic.

[0087] Comparative Example 1:

[0088] In this comparative example 1, a W90Cu10 thin sheet is provided, and its preparation method comprises the following steps:

[0089] S1. Material selection: select tungsten powder with a purity of 99.95wt.% and electrolytic copper powder with a purity of 99.95wt.% for standby use;

[0090] S2. Dry mixing: Place tungsten powder and electrolytic copper powder in a double cone powder mixer at a mass ratio of 98:2 for dry mixing;

[0091] S3, wet mixing: the material obtained in step S2 is mixed with 10 wt.% of a diluted binder, and wet mixed in a water bath at 100° C. for 1 h;

[0092] S4, drying: drying the material obtained in step S3, and then sieving it with a 50-mesh sieve, and then sieving it with a 120-mesh sieve, sieving out the material with a mesh size of 50 to 120, and then drying it for 4 hours;

[0093] S5, pressing: the material obtained in step S4 is pressed by a pressing machine, the pressing size is: 135*90*0.9mm, the pressing pressure is 120KN, and a green blank is obtained;

[0094] S6, sintering: placing the green blank obtained in step S5 on an alumina ceramic plate, cutting the Cu foil into the plane size described in S5, weighing 10wt% of the mass of the green blank (the Cu foil is weighed after cutting), fixing it on the green blank for push boat sintering, the sintering atmosphere is hydrogen obtained by decomposing ammonia, the sintering temperature is 1495°C, the push boat speed is 2.8mm / min, and then cooling is performed;

[0095] S7, rolling: the material obtained in step S6 is rolled, with a total deformation of 18%, wherein the deformation of each pass is 2%, and a total of 9 rollings are performed to obtain a W90Cu10 sheet with a thickness of 0.7 mm and a density of 98.5 wt.%.

[0096] Comparative Example 2:

[0097] In Comparative Example 2, a W90Cu10 thin sheet is provided, and its preparation method comprises the following steps:

[0098] S1. Material selection: select tungsten powder with a purity of 99.95wt.% and electrolytic copper powder with a purity of 99.95wt.% for standby use;

[0099] S2. Dry mixing: Place tungsten powder and electrolytic copper powder in a double cone powder mixer at a mass ratio of 90:10 for dry mixing;

[0100] S3, wet mixing: the material obtained in step S2 is mixed with 10 wt.% of a diluted binder, and wet mixed in a water bath at 100° C. for 1 h;

[0101] S4, drying: drying the material obtained in step S3, and then sieving it with a 50-mesh sieve, and then sieving it with a 120-mesh sieve, sieving out the material with a mesh size of 50-120 mesh, and then drying it for 4 hours;

[0102] S5, pressing: the material obtained in step S4 is pressed by a pressing machine, the pressing size is: 135*90*1.8mm, the pressing pressure is 120KN, and a green blank is obtained;

[0103] S6, sintering: placing the green blank obtained in step S5 on an alumina ceramic plate for push-boat sintering, the sintering atmosphere is hydrogen obtained by decomposing ammonia, the sintering temperature is 1495°C, the push-boat speed is 2.8 mm / min, and then cooling is performed;

[0104] S7, rolling: the material obtained in step S6 is rolled, with a total deformation of 20%, wherein the deformation of each pass is 2%, and a total of 10 rollings are performed to obtain a W90Cu10 sheet with a thickness of 1.45 mm and a density of 98.2 wt.%.

[0105] The size and thermal properties of the W90Cu10 flakes obtained in Example 1, Comparative Examples 1 and 2 are listed in Table 1.

[0106] Table 1. Properties of tungsten copper sheets of Example 1 and Comparative Examples 1-3

[0107]

[0108] In summary, the tungsten film prepared by the tungsten-containing metal slurry provided by the present invention has a high solid content, a tungsten mass fraction of up to 95wt.%, a thickness as low as 0.5mm, and a width that can be arbitrarily converted within 10-500mm, which can meet the process requirements of die cutting, patterning, and lamination pressing; its hardness is lower than 30HA, the tensile strength is as high as 20MPa, and the elongation at break is as high as 350%, with excellent flexibility and mechanical properties. The tungsten-copper thin sheet material product obtained by copper coating the tungsten film can achieve a density of more than 98.8wt.% without complicated deformation processing and large deformation, and its thermal conductivity can reach 140-350W / m·K, and the thermal expansion coefficient is as low as 5.90-8.5*10 -6 / K(70W30Cu-95W5Cu). In addition, the present invention does not require a separate degreasing process, the process is short, energy-saving and environmentally friendly, and the sintered carbon content is less than 0.008wt.%.

[0109] Embodiment 2:

[0110] In this embodiment, a 0.1 mm W90Cu10 thin sheet is provided, and the preparation method thereof comprises the following steps:

[0111] S1. Select tungsten powder: the tungsten powder is ordinary tungsten powder with a particle size D50 of 1-3μm, and it is ready for use;

[0112] S2, film-forming agent configuration: select 100 parts of waterborne polyurethane composition (including UW-1527DF, UW-1614AF, PEG400, wherein the mass ratio of UW-1527DF, UW-1614AF, PEG400 is 70:30:10), 0.8 parts of surfactant (dodecyl alcohol), 0.8 parts of dispersant (sodium polyacrylate), 0.8 parts of wetting agent (alkyl sulfate), 0.8 parts of leveling agent (organic silicon), 1.0 parts of defoaming agent BYK-051, and 25 parts of deionized water;

[0113] S3, metal slurry preparation: stir and disperse the materials of S1 and S2,

[0114] Among them, the material of S1 is 85 parts, the material of S2 is 13 parts, and the thickener (bentonite) is 2 parts;

[0115] S4, preparation of tungsten film: the material obtained in step S3 is coated into a film by tape casting process, the wet film thickness is 0.23 mm, the coating width is 350 mm, and it is dried at 65°C to obtain a tungsten film coil with a thickness of 0.16 mm; the performance of the tungsten film obtained in this embodiment is characterized, and it is found that the solid content is relatively high, and the mass fraction of tungsten is about 93wt%;

[0116] S5, tungsten film processing: the tungsten film coil obtained in step S4 is die-cut to obtain a tungsten film blank with a size of 350*150 mm;

[0117] S6, sintering treatment: the tungsten film blank obtained in step S5 is placed on an alumina ceramic plate, and the Cu foil is cut into the plane size described in S4 according to the mass ratio of tungsten to copper (W:Cu=90:10) and fixed on the tungsten film blank for push boat sintering. The sintering atmosphere is hydrogen obtained by decomposing ammonia, the sintering temperature is 1480°C, the push boat speed is 2.0mm / min, and then cooled to obtain a 90 tungsten copper sintered blank with a thickness of 0.14mm;

[0118] S7, rolling treatment: rolling the material obtained in step S6, with a total rolling deformation of 25%, a deformation of 1-2% per pass, and 15 rolling passes, to obtain a W90Cu10 tungsten copper ultra-thin sheet with a thickness of 0.1 mm and a density of 98.7%.

[0119] Embodiment 3:

[0120] This embodiment provides a 0.1 mm W80Cu20 thin sheet and a preparation method thereof, comprising the following steps:

[0121] S1. Select tungsten powder: the tungsten powder is ordinary tungsten powder with a particle size D50 of 1-3μm, and it is ready for use;

[0122] S2, film-forming agent configuration: select 100 parts of waterborne polyurethane composition (including UW-1527DF, UW-1614AF, PEG400, wherein the mass ratio of UW-1527DF, UW-1614AF, PEG400 is 65:25:8), 1.0 part of surfactant (sodium hexametaphosphate), 0.5 part of dispersant (monoethanolamine), 0.5 part of wetting agent (silicone oil type wetting agent), 0.5 part of leveling agent (modified acrylate), 0.8 part of defoaming agent (TEGO Foamex810), and 25 parts of deionized water;

[0123] S3, metal slurry preparation: stir and disperse the materials of S1 and S2,

[0124] Among them, the material of S1 is 85 parts, the material of S2 is 13 parts, and the thickener (associative waterborne polyurethane) is 2 parts;

[0125] S4, preparation of tungsten film: the material obtained in step S3 is coated into a film by a tape casting process, the wet film thickness is 0.2 mm, the coating width is 350 mm, and it is dried at 65° C. to obtain a tungsten film coil with a thickness of 0.14 mm; the performance of the tungsten film obtained in this embodiment is characterized, and it is found that the solid content is relatively high, and the mass fraction of tungsten is about 93wt%;

[0126] S5, tungsten film processing: the tungsten film coil obtained in step S4 is die-cut to obtain a tungsten film blank with a size of 350*150 mm;

[0127] S6, sintering treatment: the tungsten film blank obtained in step S5 is placed on an alumina ceramic plate, and the Cu foil is cut into the plane size described in S4 according to the mass ratio of tungsten to copper (W:Cu=80:20) and fixed on the tungsten film blank for push boat sintering. The sintering atmosphere is hydrogen obtained by decomposing ammonia, the sintering temperature is 1460°C, the push boat speed is 3.0mm / min, and then cooled to obtain a 80 tungsten copper sintered blank with a thickness of 0.12mm;

[0128] S7, rolling treatment: rolling the material obtained in step S6, with a total rolling deformation of 15%, a deformation of 1-4% per pass, and 7 rolling passes, to obtain a W80Cu20 tungsten copper ultra-thin sheet with a thickness of 0.1 mm and a density of 99.4%.

[0129] Embodiment 4:

[0130] This embodiment provides a 0.1 mm W85Cu15 thin sheet, and the preparation method thereof comprises the following steps:

[0131] S1. Select tungsten powder: the tungsten powder is ordinary tungsten powder with a particle size D50 of 1-3μm, and it is ready for use;

[0132] S2, film-forming agent configuration: select 100 parts of waterborne polyurethane composition (including UW-1527DF, UW-1614AF, PEG400, wherein the mass ratio of UW-1527DF, UW-1614AF, PEG400 is 60:20:10), 1.0 part of surfactant (sodium tripolyphosphate), 0.5 part of dispersant (sodium polyacrylate), 0.5 part of wetting agent (carboxylic acid soap), 0.5 part of leveling agent (fluorinated polymer), 0.8 part of defoamer (DF-1030), and 25 parts of deionized water;

[0133] S3, metal slurry preparation: stir and disperse the materials of S1 and S2,

[0134] Among them, the material of S1 is 85 parts, the material of S2 is 13 parts, and the thickener (sodium silicate) is 2 parts;

[0135] S4, preparation of tungsten film: the material obtained in step S3 is coated into a film by tape casting process, the wet film thickness is 0.21 mm, the coating width is 350 mm, and it is dried at 65°C to obtain a tungsten film coil with a thickness of 0.15 mm; the performance of the tungsten film obtained in this embodiment is characterized, and it is found that the solid content is high, and the mass fraction of tungsten is about 93wt%;

[0136] S5, tungsten film processing: the tungsten film coil obtained in step S4 is die-cut to obtain a tungsten film blank with a size of 350*150 mm;

[0137] S6, sintering treatment: the tungsten film blank obtained in step S5 is placed on an alumina ceramic plate, and the Cu foil is cut into the plane size described in S4 according to the mass ratio of tungsten to copper (W:Cu=85:15) and fixed on the tungsten film blank for push boat sintering. The sintering atmosphere is hydrogen obtained by decomposing ammonia, the sintering temperature is 1470°C, the push boat speed is 2.5mm / min, and then cooled to obtain a 90 tungsten copper sintered blank with a thickness of 0.13mm;

[0138] S7, rolling treatment: rolling the material obtained in step S6, with a total deformation of 20%, a deformation of 1-3% per pass, and 10 rolling passes, to obtain a W85Cu15 tungsten copper ultra-thin sheet with a thickness of 0.1 mm and a density of 99.1%.

[0139] Embodiment 5:

[0140] In this embodiment, a 0.2 mm W70Cu30 thin sheet is provided, and the preparation method thereof comprises the following steps:

[0141] S1. Select tungsten powder: the tungsten powder is ordinary tungsten powder with a particle size D50 of 1-3μm, and it is ready for use;

[0142] S2, film-forming agent configuration: select 100 parts of waterborne polyurethane composition (including UW-1527DF, UW-1614AF, PEG400, wherein the mass ratio of UW-1527DF, UW-1614AF, PEG400 is 65:30:5), 1.0 part of surfactant (dioctadecyl dimethyl ammonium chloride), 0.5 part of dispersant (aryl phosphate), 0.5 part of wetting agent (phosphate), 0.5 part of leveling agent (polyacrylate), 0.8 part of defoamer (DC 2000), and 25 parts of deionized water;

[0143] S3, metal slurry preparation: stir and disperse the materials of S1 and S2,

[0144] Among them, the material of S1 is 90 parts, the material of S2 is 8 parts, and the thickener (hydroxypropyl methylcellulose) is 2 parts;

[0145] S4, preparation of tungsten film blank: the material obtained in step S3 is coated by tape casting process to form a film, the wet film thickness is 0.35 mm, the coating width is 350 mm, and it is dried at 65°C to obtain a tungsten film coil with a thickness of 0.25 mm; the performance of the tungsten film obtained in this embodiment is characterized, and it is found that the solid content is high, and the mass fraction of tungsten is about 95wt%;

[0146] S5, sintering treatment: the tungsten film blank obtained in step S4 is placed on an alumina ceramic plate, and the Cu foil is cut into the plane size described in S4 according to the mass ratio of tungsten to copper (W:Cu=70:30) and fixed on the tungsten film blank for push boat sintering. The sintering atmosphere is hydrogen obtained by decomposing ammonia, the sintering temperature is 1450°C, the push boat speed is 3.0mm / min, and then cooled to obtain a 90 tungsten copper sintered blank with a thickness of 0.23mm;

[0147] S6, rolling treatment: rolling the material obtained in step S5, with a total rolling deformation of 10%, a deformation of 1-3% per pass, and 5 rolling passes, to obtain a W70Cu30 tungsten copper ultra-thin sheet with a thickness of 0.2 mm and a density of 99.6%.

[0148] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. A tungsten-containing metal slurry, characterized in that: include: Tungsten powder, organic film former and thickener; The organic film-forming agent includes an aqueous polyurethane composition; The mass ratio of tungsten powder, organic film-forming agent and thickener is (80-95):(5-20):(2-5).

2. The metal slurry according to claim 1, characterized in that: The D50 particle size of the tungsten powder is 0.5-6 μm, preferably 0.8-5 μm, more preferably 1-3 μm; and / or The purity of the tungsten powder is ≧99.50%, preferably ≧99.90%, and more preferably ≧99.95%.

3. The metal slurry according to claim 1, characterized in that: The organic film-forming agent further comprises one or more of a surfactant, a dispersant, a wetting agent, a leveling agent, and a defoaming agent.

4. The metal slurry according to claim 3, characterized in that: The mass ratio of the aqueous polyurethane composition to the surfactant is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), more preferably (100-105):(0.5-1); and / or The mass ratio of the aqueous polyurethane composition to the dispersant is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), more preferably (100-105):(0.5-1); and / or The mass ratio of the aqueous polyurethane composition to the wetting agent is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), more preferably (100-105):(0.5-1); and / or The mass ratio of the aqueous polyurethane composition to the leveling agent is (80-120): (0.2-1.5), preferably (85-110): (0.3-1.3), more preferably (100-105): (0.5-1); and / or The mass ratio of the aqueous polyurethane composition to the defoamer is (80-120):(0.2-1.5), preferably (85-110):(0.3-1.3), more preferably (100-105):(0.5-1); and / or The mass ratio of the aqueous polyurethane composition to the deionized water is (80-120):(1-40), preferably (85-110):(2-35), and more preferably (100-105):(3-30).

5. The metal slurry according to claim 3, characterized in that: The dispersant comprises one or more of sodium polyacrylate, polyvinyl pyrrolidone, tributyl phosphate, alkyl phosphate, aryl phosphate, monoethanolamine, diethanolamine, sodium silicate, and trisodium phosphate; and / or The wetting agent includes one or more of alkyl sulfates, sulfonates, fatty acids or fatty acid ester sulfates, carboxylic acid soaps, phosphates, silicone oil-type wetting agents, aqueous wetting agents, and organic solvent wetting agents; and / or The leveling agent includes one or more of silicone, polyacrylate, fluorine-containing polymer, and modified acrylate; and / or The defoamer comprises one or more of an organosilicon defoamer, a polyether defoamer, a fatty acid and its derivatives defoamer, a polyacrylate defoamer, and a mineral oil defoamer; and / or The thickener includes one or more of polyvinyl alcohol, polyacrylic acid, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, aluminum silicate, sodium silicate, bentonite, and associative waterborne polyurethane.

6. A method for preparing a tungsten copper ultra-thin sheet, comprising the steps of: The tungsten-containing metal slurry according to any one of claims 1 to 5 is coated to form a film, and then dried to obtain a tungsten film blank; The tungsten film blank is copper-coated, then degreased, sintered, and cooled to obtain a tungsten-copper alloy; The tungsten-copper alloy is rolled to obtain the tungsten-copper ultra-thin sheet.

7. The method according to claim 6, characterized in that: The manufacturing process of the tungsten film blank further includes: after the drying, a tungsten film coil is obtained, and the tungsten film coil is used to prepare a tungsten film blank with a preset shape; preferably, The tungsten film coil is processed by one or more of the following methods: die cutting, patterning, lamination pressing, etc., to obtain the tungsten film blank with a preset shape.

8. The method according to claim 6, characterized in that: The copper cladding method is to lay copper foil flat on the upper surface of the tungsten film blank, wherein the size of the copper foil is consistent with the size of the tungsten film blank.

9. The method according to claim 6, characterized in that: The total deformation of the rolling is 1-40%, preferably 3-30%, more preferably 5-25%; and / or The deformation amount of each rolling pass is 0.2-8%, preferably 0.5-6%, more preferably 1-5%; The number of rolling passes is 1-40 times, preferably 1-30 times, and more preferably 1-20 times.

10. A use of the tungsten copper ultra-thin sheet as claimed in any one of claims 6 to 9, characterized in that: The tungsten copper ultra-thin sheet is applied to the fields of heat sink materials and electronic packaging materials, especially to 4-12 inch microelectronic packaging.